Communication Excellence: How to Develop, Manage and Lead Exceptional Communications - Tench, Ralph and Verhoeven, Piet and Zerfaß, Ansgar and Moreno, Ángeles (SpringerLink Bücher, 2017)
"This powerful, practical and highly relevant book is a must read for both communication scholars and practitioners." - Donald K. Wright, College of Communication, Boston University, USA "This book provides a compelling case that effective communication for an organization is as much about the outside-in as the inside-out perspective” - Maximilian Schoeberl, Executive Vice President & Director Corporate Affairs, BMW Group “This is a powerhouse book of inspiring frameworks, empirical insights and useful case studies that simply work” - Xianhong Chen, President, Public Relations Society of China & Professor, Huazong University of Science and Technology, China Exploring the implications of 10 years of data from more than 22,000 communication professionals across Europe, combined with case studies and interviews with chief communication officers from top European companies and organisations, this book provides an insight into how to build, develop and lead excellent communication. Communication Excellence presents a culmination of research and best practice models, covering strategic communication, the impact on reputation, crisis, mediatisation, organisational culture, new digital, social and mobile media as well as the development of professionalization. Providing clear guidance on the difference between normal and excellent communications departments, the book shows readers how communication can effectively influence and support the organisation and positively fit within the business strategy of today’s global and changing markets. The study behind this book, the European Communication Monitor, is known as the most comprehensive provider of reliable data in the communication field worldwide
https://katalog.adlr.link/Record/0-1657594408